MEDIA SOSIAL DAN LITERASI KEBENCANAAN DI BALI - Ras Amanda Gelgel, Ni Made (Interaksi: Jurnal Ilmu Komunikasi, 2020)
After a large, deadly explosive and effusive eruption during 1963-64, Indonesia's Mount Agung on Bali remained quiet until a new eruption began in November 2017 until 2019. Alert Level III (of four levels) remained in effect throughout the period with a 4 km exclusion radius around the volcano.  Massive hysteria occurred when alert level reach the highest level (level IV). The situation get worsed when misinformation has been spreading in social media about Mt. Agung. This research discussing how literate was the Balinese in consuming disaster information.  The research was in 2018 used positivisim paradigm. Data collected by using questionnaire with  410 sample from all the regency in Bali Province. Main theory was dependence theory. The result are (1) social media became the most sourceful media to gain disaster information, (2) but the Balinese people didn’t verify the information they gained (3) 30 percent respondent shared the information without verification. It showed Balinese’s literacy in gaining disaster information need to be improve and have a high dependence in using social media.